2019
DOI: 10.5222/mmj.2019.34032
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Anxiety Among Physicians Working in Emergency Departments and Other Clinics in Turkey: A Cross-Sectional Survey

Abstract: Objective: Physicians are exposed to various emotional and physical stressors in their working environment. Emergency departments are particularly stressful working environments. This study aimed to determine the frequency of anxiety among emergency physicians (EP) and other medical specialists. Methods: This cross-sectional survey included voluntarily participated physicians working in hospitals in Turkey. Physicians were grouped based on their Beck Anxiety Inventory (BAI) scores and their characteristics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Similarly, anxiety levels of female physicians were reported to be higher than male physicians 18,19 . In a cross‐sectional survey, female physicians had higher anxiety levels than males and have also been reported to be exposed to certain stress factors related to discrimination, lack of role models and support, role stress and overload 20 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, anxiety levels of female physicians were reported to be higher than male physicians 18,19 . In a cross‐sectional survey, female physicians had higher anxiety levels than males and have also been reported to be exposed to certain stress factors related to discrimination, lack of role models and support, role stress and overload 20 …”
Section: Discussionmentioning
confidence: 99%
“…18,19 In a crosssectional survey, female physicians had higher anxiety levels than males and have also been reported to be exposed to certain stress factors related to discrimination, lack of role models and support, role stress and overload. 20 Biological factors, such as the variation in ovarian hormone levels, may contribute to the increased prevalence of depression and anxiety in women. 21 In our study, female physicians reported more severe symptoms of anxiety in all measurements, consistent with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to stress factors in the workplace has been associated with a number of adverse physical and mental health problems 4 . Chronic job stress in emergency health care workers is associated with occupational dissatisfaction, physical fatigue, burnout and posttraumatic stress symptoms 5 - 8 .…”
Section: Introductionmentioning
confidence: 99%